The study of using Tannin extracts from Indian almond leaves to produce acne patches from discarded silkworm cocoons - Pimpichcha Uttarapong; Natcha Theerapiboon; Pikulrat Aramkajorndej; Viwat Sutana (Malaysia Journal of Invention and Innovation, 2024)
This research focuses on utilizing Tannin extract from Indian Almond leaves to develop acne patches made from discarded silkworm cocoons. The goal is to explore the antibacterial properties of Tannin in addressing acne and to create a natural, eco-friendly skincare product. The process began by extracting Tannin from the Indian Almond leaves, which were boiled in distilled water and then diluted to different concentrations (100%, 50%, 25%, and 12.5%). The antibacterial effectiveness was tested using the disc diffusion method under both aerobic and anaerobic conditions. For comparison, antibiotics like Azithromycin, Roxithromycin, and Vancomycin were used as controls, while distilled water served as the negative control. The results indicated that the 100% Tannin extract had the highest antibacterial efficiency under anaerobic conditions, comparable to Vancomycin. Roxithromycin was the most effective in both oxygen conditions, but the Tannin extract, particularly at 100% concentration, showed promising results as well. In the next phase, discarded silk fibers were processed to extract Fibroin, which was used to create acne patches. Two types of patches were made: one with just Fibroin and the other with a 1:1 mix of Fibroin and Tannin extract. These patches were tested under the same oxygen conditions to assess their antibacterial properties, with Roxithromycin as the control. The results showed that the Fibroin-Tannin acne patch performed similarly to Roxithromycin in inhibiting acne-causing bacteria, demonstrating its potential as a natural alternative for acne treatment. In conclusion, the combination of Fibroin from discarded silkworm cocoons and Tannin extract from Indian Almond leaves can produce an effective, environmentally friendly acne treatment. This study not only highlights a sustainable approach to reducing waste from the silk and agricultural industries but also provides a viable option for natural skincare solutions that benefit both consumers and the environment.